Algebratic Properties Of Residu Quadratic Codes Expanded - Kusbudiono, Kusbudiono; Juliyanto, Bagus (Majalah Ilmiah Matematika dan Statistika, 2017)
In code theory one of the important code types is binary code. At binary field till, there is a residu quadratic and a permutation defined with residu quadratic can form a code called residu quadratic code. This code can be extended. In this paper, we discuss the propertis of group of it.